EFEKTIVITAS LATIHAN ERGONOMI TERHADAP KUALITAS TIDUR PETANI: INTERVENSI BERBASIS KOMUNITAS - Ridha Wahdini; Nadia Sintia Wardany; Agni Laili Perdani; Irma Darmawati; Slamet Rohaedi (Jurnal Porkes, 2026)
The problem in this study is that farmers are at high risk of musculoskeletal disorders due to non-ergonomic work postures, which have an impact on poor sleep quality. Community-based non-pharmacological interventions to address this problem in the Indonesian farming population are still very limited. This study aims to evaluate the effect of a community-based ergonomic exercise program on improving sleep quality among farmers. The method used in this study is a one-group pretest-posttest quasi-experimental design without a control group. A total of 85 farmers were selected using purposive sampling in West Bandung Regency. The intervention consisted of ergonomic exercises (stretching, core muscle strengthening, relaxation) for 10-15 minutes per session, 5 times a week, for 2 weeks. Sleep quality was measured using the Indonesian version of the Pittsburgh Sleep Quality Index (PSQI). Data analysis was performed using the Wilcoxon signed-rank test. The results showed a significant decrease in the global PSQI score from 12.92 (SD=4.71) to 11.61 (SD=4.29) with a mean difference of -1.31 (95% CI: -1.89 to -0.73; p<0.001). The effect size was in the moderate category (r=0.359). The proportion of respondents with good sleep quality increased from 9.4% to 22.4%. The discussion in this study is that ergonomic exercises are associated with improved sleep quality through muscle tension reduction, autonomic nervous system modulation, and increased postural awareness. These findings are consistent with previous studies in working populations. However, the absence of a control group limits causal conclusions. In conclusion, community-based ergonomic exercise programs show potential as a feasible and acceptable promotive-preventive intervention to improve sleep quality among farmers. Further research with an RCT design and longer duration is needed to confirm causal effectiveness.